Microstructural evolution and IMCs growth behavior of Sn-58Bi-0.25Mo solder joint during aging treatment. (22nd February 2018) - Yang, Li; Zhu, Lu; Zhang, Yaocheng; Zhou, Shiyuan; Xiong, Yifeng; Wu, Pengcheng
Abstract: The microstructural evolution and IMCs growth behavior of Sn-58Bi and Sn-58Bi-0.25Mo solder joints were investigated. The results showed that the microstructure is coarsened, the IMCs layer thickness is increased and the tensile strength of Sn-58Bi and Sn-58Bi-0.25Mo solder joints is decreased with increasing aging time and temperature. Aging temperature is the key factor that causes the excessive IMCs growth of the solder joint compared with aging time, and the activation energy of IMCs layer growth of Sn-58Bi and Sn-58Bi-0.25Mo solder joints is 48.94 kJ mol −1 and 53.79 kJ mol −1, respectively. During the aging treatment, the microstructure of Sn-58Bi solder joint is refined by adding Mo nanoparticles, and the appropriate IMCs layer thickness and improved mechanical properties are obtained by Sn-58Bi-0.25Mo solder joint.